THE "PACKAGE" OF HUNTING IN LA PAMPA AND ITS TERRITORIAL IMPLICATIONS - María Eugenia Comerci (Boletín Geográfico)
In the framework of the expansion of capital in Argentina, the province of La Pampa is positioned as the first producer of hunting reserves and fields registered for that activity, with more trophies and tourists. However, this item is not limited to the practice of hunting both native and introduced wildlife. The "package" of the game involves access to the purchase of the land by foreign investors, a new enhancement of the spinal ecoregion by the abundance of wildlife and the possibility of hunting with a more flexible legislation than the existing one in bordering provinces. In this context, hunting attracts extra-local capital and is promoted by various public organisms. The accumulation of spatial images that appear in tourist documents and investment guides express certain representations about the hunting activity and certain territorial readings about the province of La Pampa, produced in situated contexts. In this framework, it is interesting to address in this article how the activity is promoted and what the "package" of hunting implies territorially. For the development of the work, the empirical basis was built with official statistical sources that were triangulated with interviews to owners of game reserves, hunting guides and hunting operators, carried out in different opportunities between 2013 and 2017. The research indicates that the provincial government has intervened actively and in a sustained manner from different agencies over time. These elements were generating a territorial imaginary around hunting with different intentions according to the programs and institutions that promoted it. Likewise, private agents have promoted the activity together with the sale of the land. The business is not limited to the purchase and sale of fields and the opening of game reserves, but also to the establishment of breeding sites, as an associated and alternative activity. The progress of these rural estates coincides with the growth of foreign ownership of land and the arrival of new agents in the Pampa region, with a business profile, and, many of them, articulated in global networks.